Corrigendum - JAM, JAM (Jurnal Aplikasi Manajemen, 2024)
Corrigendum to “The Role of Women Merchants in Increasing Family’s Income (A Case Study on Indigenous Papuan Women Merchants)“ [JAM: Jurnal Aplikasi Manajemen, 14(4), 641-649]